The chemistry of the wattle tannins - Roux, David Gerhardus (Rhodes University, Faculty of Science, Department of Chemistry, 1953)
Four species of acacia of Auatralian origin are associated with the wattle industry in South Africa. Black wattle, Acacia mollissima willd., is the most important of these and is today almost exclusively cultivated. The tree grows successfully only in a limited area of rich soil and high rainfall and is easily affected by adverse conditions caused by insect pests, frost damage and drought. Expansion of the area under cultivation is therefore, not feasible, although the world demand for vegetable extracts far exceeds the available supply. The remaining species such as green (Acacia decurrrens willd.) and silver wattles (Acacia dealbata Link.) possess many desirable characteristics which resist such adverse factors. Their barks, however, give reddish extracts, which are considered unsuitable for tannery usage because of the red colour they impart to the leather. Hybridisation studies, involving the crossing of green and silver wattle with the black, and aimed at produc1ng progenies containing many of the desirable characterlstics of the parent plants, are thus a natural result and have been in progress for a considerable period. Summary, p. i.
Keywords: Tannin plants; Tannins; Wattles (Plants)